2003
DOI: 10.1103/physrevlett.90.055501
|View full text |Cite
|
Sign up to set email alerts
|

Light Transport through the Band-Edge States of Fibonacci Quasicrystals

Abstract: The propagation of light in nonperiodic quasicrystals is studied by ultrashort pulse interferometry. Samples consist of multilayer dielectric structures of the Fibonacci type and are realized from porous silicon. We observe mode beating and strong pulse stretching in the light transport through these systems, and a strongly suppressed group velocity for frequencies close to a Fibonacci band gap. A theoretical description based on transfer matrix theory allows us to interpret the results in terms of Fibonacci b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
179
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(184 citation statements)
references
References 35 publications
5
179
0
Order By: Relevance
“…The Fibonacci multilayer structure is the well-known 1D quasiperiodic structure, its electronic properties has been well-studied since the discovery of the quasi-crystalline phase in 1984 [22]. Wave through a structure in the Fibonacci sequence had also been studied in past decade, and recently the resonant states at the band edge of a photonic structure in the Fibonacci sequence are studied experimentally [23]. Studies of various aspects of wave propagation in the Fibonacci quasiperiodic structures carried out in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The Fibonacci multilayer structure is the well-known 1D quasiperiodic structure, its electronic properties has been well-studied since the discovery of the quasi-crystalline phase in 1984 [22]. Wave through a structure in the Fibonacci sequence had also been studied in past decade, and recently the resonant states at the band edge of a photonic structure in the Fibonacci sequence are studied experimentally [23]. Studies of various aspects of wave propagation in the Fibonacci quasiperiodic structures carried out in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In one dimension, the states in quasiperiodic multilayers and the evolution of spectrum with sample size have been extensively studied. [1][2][3][4] Many interesting phenomena such as critical states and singular continuous spectrum have been discovered. 1,2 In two dimensions, recently, it has been shown that large full band gaps can be opened in photonic quasicrystals with small dielectric contrast due to the high rotational symmetry of a quasiperiodic structure.…”
Section: Introductionmentioning
confidence: 99%
“…16 Strongly suppressed group velocity has also been observed at the band-edge states of Fibonacci photonic quasicrystals by ultrashort pulse interferometry. 4 Secondly, great achievements have been made in the applications of the band-edge states in photonic crystals. [25][26][27][28][29] However, recent studies showed that the band-edge states in photonic quasicrystals can support various applications with novel and promising properties that are unrealizable by using the band-edge states in photonic crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common quasi-periodic structure is Fibonacci sequence [12][13][14][15]. Fibonacci sequence multilayer present a discrete Fourier spectrum characterized by self-similar Bragg peak.…”
Section: Introductionmentioning
confidence: 99%